To act or not to act - a sense of control is important for people with chronic obstructive pulmonary disease to increase physical activity : grounded theory study - Marklund, Sarah; Sörlin, Ann; Stenlund, Tobias; Wadell, Karin; Nyberg, Andre (JMIR Formative Research, 2023)
Background: Among people with chronic obstructive pulmonary disease (COPD), low level of daily physical activity (PA) is the main risk factor for developing cardiovascular, metabolic, and musculoskeletal comorbidities. Increasing PA in people with COPD is complex as PA behavior itself is complex and multifaceted, including personal, physiological, and psychologicalelements as well as social and environmental factors. Although eHealth solutions such as web-based support or websites haveshown positive effects on PA in people with COPD, the results are inconclusive, and it is still unclear how eHealth solutionsmight be used to support positive changes in PA behavior in people with COPD. Objective: This study aimed to explore the perceptions of increasing objective PA when using a web-based eHealth tool amongpeople with COPD. Methods: This study was part of a pragmatic randomized controlled trial with in-depth interviews between the 3- and 12-month follow-ups. The methodology used was constructivist grounded theory. All sampling included participants from the randomized controlled trial intervention group, that is, participants who had access to the eHealth tool in question and agreed to be contacted for an in-depth interview. Inclusion of participants continued until data saturation was reached, resulting in an inclusion of 14 (n=8, 57% women) participants aged between 49 and 84 years and living in 8 municipalities in Middle and Northern Sweden. Two interviews were conducted face-to-face, and the remaining interviews were conducted via telephone. All interviews were recorded using a Dictaphone. Results: The analysis resulted in 3 main categories: welcoming or not welcoming action, having or lacking resources, and lowering the threshold. The first 2 categories contain barriers and facilitators, whereas the third category contains only facilitators. The categories lead to the more latent theme Perceiving enough control to enable action, meaning that it seems that perceiving the right amount of control is essential to ...